2004
DOI: 10.1128/aem.70.4.2354-2366.2004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gene Expression in Escherichia coli in Response to Changes of Growth-Limiting Nutrient in Chemostat Cultures

Abstract: Studies of steady-state metabolic fluxes in.8% of a total of 4,071 genes investigated, especially those involved in amino acid metabolism, central carbon and energy metabolism, transport system and cell envelope, were observed to be differentially expressed between the two nutrient-limited cultures. One important characteristic of E. coli grown under nutrient limitation was its capacity to scavenge carbon or nitrogen from the medium through elevating the expression of the corresponding transport and assimilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
136
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(154 citation statements)
references
References 36 publications
15
136
2
1
Order By: Relevance
“…For example, transcript levels for genes for a number of ribosomal proteins, such as rplL and rpsC, were approximately 20-fold lower during growth on sediments. Transcript levels for protein synthesis genes are typically lower in microorganisms growing at slower growth rates (Gonzalez et al, 2002;Hua et al, 2004;Boccazzi et al, 2005). Thus, these results are consistent with the fact that G. uraniireducens grows sevenfold slower on sediments relative to fumarate (DE Holmes, manuscript in preparation).…”
Section: Resultssupporting
confidence: 73%
“…For example, transcript levels for genes for a number of ribosomal proteins, such as rplL and rpsC, were approximately 20-fold lower during growth on sediments. Transcript levels for protein synthesis genes are typically lower in microorganisms growing at slower growth rates (Gonzalez et al, 2002;Hua et al, 2004;Boccazzi et al, 2005). Thus, these results are consistent with the fact that G. uraniireducens grows sevenfold slower on sediments relative to fumarate (DE Holmes, manuscript in preparation).…”
Section: Resultssupporting
confidence: 73%
“…TBAR determination suggested that lipid peroxidation does not occur in this condition, indicating that toxic YqhD substrates are not generated (unpublished results). 5 Transcription activation of the yqhD gene has been observed in cells treated with the oxidant Curvularia haloperoxidase system (23) when exposed to cold shock (21) or when grown in a limited-nutrient medium (22). Here we demonstrate that yqhD is also induced in cells exposed to conditions favoring lipid peroxidation, as are treatments with the ROS elicitors K 2 TeO 3 , H 2 O 2 , or paraquat or with the membrane lipid-peroxidating compound t-BOOH.…”
Section: Figure 3 Oxidized Proteins In E Coli a Sds-page Showing mentioning
confidence: 53%
“…Based mainly on the bound coenzyme, NADP(OH) 2 , they proposed a putative relationship between YqhD and oxidative stress. Genomic and proteomic studies have shown that YqhD is expressed in E. coli after exposure to stress conditions such as cold shock (21), nutrient starving (22), and oxidative stress generated by the Curvularia peroxidase system (23). YqhD has several features similar to AdhE, an alcohol/aldehyde dehydrogenase involved in fermentative metabolism in E. coli for which an antioxidant function under aerobic conditions has been proposed (24).…”
mentioning
confidence: 99%
“…Saccharomyces cerevisiae (Boer et al 2003;Wu et al 2004) and E. coli (Hua et al 2004). This phenomenon should be considered when studying the effects of a chemical effector such as toluene at the transcriptome level.…”
Section: Resultsmentioning
confidence: 99%